ANALISIS PERHITUNGAN DAN PENCATATAN AKUNTANSI PAJAK PENGHASILAN ATAS BUNGA DEPOSITO DAN TABUNGAN NASABAH PADA PT. BANK SYARIAH MANDIRI CABANG MANADO - Tingginehe, Nurgita; Sondakh, Jullie J.; Pontoh, Winston (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The contribution to the state and the source of our income comes from taxes. One of the final income tax objects is the interest rate on deposits and customer saving. This study aims to find out how to calculation and record of accounting deposit interest rate and savings customers at PT. Bank Syariah Mandiri Branch Manado. The analytical method used is descriptive analysis of Â research data obtained from interviews and literature studies. The results of the study show the count of income tax on interest deposits customers from PT. Bank Syariah Mandiri Branch Manado has been accordance with goverment regulations No.131 of 2000 and KMK-51/KMK.04/2001. And accounting records has been accordance with accounting PSAK 101 Syariah. PT. Bank Syariah Mandiri Branch Manado must improve service quality Â for improvement costumers.Keywords:Calculation, Recording, Deposit Interest, Customer Savings